LEGAL STATUS OF THE SUPREME COURT OF THE REPUBLIC OF POLAND - Khotsianovska, Natalia; Kostenko, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: the article is aimed at researching the legal status of the Supreme Court of the Republic of Poland under the current national legislation Research methods: the article uses the dialectical method of cognition, general scientific methods and special research methods. In particular, the structural and function method, deductive method and the method of scientific forecasting. Results: the author outlines the peculiarities of the legal status of the Supreme Court of the Republic of Poland under the current national legislation and its role at the modern stage of development; identifies the factors that influence the judicial reform initiated by the European Union; identifies the conflict of interest between the acts of the European Union and the national legislation of the Republic of Poland in relation to certain issues of determining the legal status of the Supreme Court; emphasises the significant role of the Supreme Court’s practice in the activities of the Supreme Court of the Republic of Poland and the forms of judicial review; it is determined that the basic principles of the legal status of the Supreme Court of the Republic of Poland are determined by the Constitution of the Republic of Poland, the Supreme Court Act, the Act on Amendments to the Supreme Court Act and some other laws of 9 June 2022, and the Order of the President of the Republic of Poland "Rules of Procedure of the Supreme Court". Discussion: the judiciary is one of the main branches of power that plays a crucial role in society, and in times of martial law, it faces new challenges. Ukraine is on a long path to reforming its judicial system. Similar processes are taking place in the Republic of Poland, which is not only a member of the European Union and shares a geographical border with Ukraine but has also been a reliable ally and support for Ukraine in recent difficult years. The Supreme Court is the highest judicial body in both Ukraine and the Republic of Poland. As a result of the judicial reform, certain aspects of the legal status of the Supreme Court are subject to relevant changes. The process of studying the transformation of the legal status of the Supreme Court of the Republic of Poland is important in terms of Ukraine’s perception of positive experience for its implementation in its own judicial reform and negative experience for avoiding similar mistakes in the future, which determines the need for further research on this issue.